2018
DOI: 10.1016/j.semcdb.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Arc protein: a flexible hub for synaptic plasticity and cognition

Abstract: Mammalian excitatory synapses express diverse types of synaptic plasticity. A major challenge in neuroscience is to understand how a neuron utilizes different types of plasticity to sculpt brain development, function, and behavior. Neuronal activity-induced expression of the immediate early protein, Arc, is critical for long-term potentiation and depression of synaptic transmission, homeostatic synaptic scaling, and adaptive functions such as long-term memory formation. However, the molecular basis of Arc prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 95 publications
2
118
1
Order By: Relevance
“…Finally, Arc regulated genes associated with altered cognitive function, a characteristic of AD (Mmp13, Pdyn, Tac1, Bdnf, Nr4a2, Penk, Pltp and Ccl2). To date, presenilin 1 (Psen1) and glycogen synthase kinase 3 beta (Gsk3b) are the only AD mediators which have been reported to physically associate and interact with Arc [78][79][80] . Arc also interacts with endophilin 2/3 and dynamin and recruits them to early/recycling endosomes to traffic APP and beta secretase 1 (BACE1), crucial determinants of AD progression 80 .…”
Section: Arc Knockdown Changes the Expression Of Genes Involved In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Arc regulated genes associated with altered cognitive function, a characteristic of AD (Mmp13, Pdyn, Tac1, Bdnf, Nr4a2, Penk, Pltp and Ccl2). To date, presenilin 1 (Psen1) and glycogen synthase kinase 3 beta (Gsk3b) are the only AD mediators which have been reported to physically associate and interact with Arc [78][79][80] . Arc also interacts with endophilin 2/3 and dynamin and recruits them to early/recycling endosomes to traffic APP and beta secretase 1 (BACE1), crucial determinants of AD progression 80 .…”
Section: Arc Knockdown Changes the Expression Of Genes Involved In Thmentioning
confidence: 99%
“…6). The domain structure of Arc protein appears to rule out that it can function as a transcription factor 78 . This raises the question: how does Arc regulate transcription?…”
Section: How Does Arc Regulate Transcription?mentioning
confidence: 99%
“…Interestingly, the REM-dependent pruning and strengthening of newly formed spines after learning was dependent on the activation of the NMDAr (Fig. 4d), increased calcium signaling specifically in the dendrites related to the mnemonic trace, and CaMKII activation, which in turn, can interact with Arc [210] (for a review see [211]).…”
Section: Selective Pruning and Maintenance Of Synapses By Post-trainimentioning
confidence: 99%
“…In LTP consolidation, SUMOylated Arc forms a complex with Drebrin as well, a major regulator of cytoskeletal dynamics in dendritic spines [16]. Thus, Arc protein interacts with distinct protein partners to participate in the regulation of multiple forms of synaptic plasticity [17]. Interestingly, we previously demonstrated that HSV-1 acute infection increases Arc mRNA and protein expression in different neuronal cell lines, and the up-regulation is dependent of an active viral replicative cycle [18].…”
Section: Introductionmentioning
confidence: 99%